Bioactive Potential and Antioxidant Activity of Blood Clam (Tegillarca granosa L.) Protein for Functional Food Applications - Hasan, Tahirah; Alim, Nur; Salim, La Ode Agus (Jurnal Rekayasa Kimia & Lingkungan, 2024)
This study investigates the antioxidant potential and protein content of the blood clam (Tegillarca granosa L.), a marine species rich in bioactive compounds that could serve as a functional food source. Antioxidants play a crucial role in combating free radicals, which are linked to various degenerative diseases. This research aims to quantify the protein content and evaluate the antioxidant activity of blood clam extracts to assess their potential for functional food applications. The study utilized the Lowry method to measure protein content and the DPPH assay to assess antioxidant activity. Blood clam samples were collected from the coastal region of Pangkep, South Sulawesi. Protein levels were determined using UV-Vis spectrophotometry, while antioxidant activity was quantified by IC50 values. Results indicate that blood clams contain 21.75% protein, with an IC50 antioxidant value of 17.935 0.360 g/mL, which, while lower than ascorbic acid (IC50 = 2.34 g/mL), demonstrates substantial antioxidant activity. This studys unique contribution to the functional food field lies in identifying blood clams as a promising source of both protein and antioxidants, with potential health benefits related to oxidative stress prevention. The practical implications highlight blood clam's suitability as a natural functional food ingredient aimed at supporting overall health.